Optimizing the costs of short sea shipping : A case study for a Finnish company in forest industry - Elonen, Atte (My University, 2018)
This study is a shipping cost optimization of a forest industrial company. The case company ships its products from its mills in Sweden and Finland to Continental Europe via short sea shipping, which means shipping for relatively short distances. The most competitive distance for short sea shipping is between 1 700 and 2 500 kilometers. The current short sea shipping-chain of the case company needs improvements 2021 onwards, because of an aging ship, which will be out of traffic by then. Additionally, the case company is willing to cut its costs related to short sea shipping. In this study, a functioning future short sea shipping-chain is formed and at the same time cost savings are achieved. Shipping costs are approached through quantitative analysis and constructive research methodology, which is based on previous literature of shipping costs. Literature review also covers the shipping market of forest products, definition of short sea shipping and its integration to intermodal transport chains and future maritime regulation from the perspective of an exporting forest company. In this study, cost savings are achieved by finding the lowest euro per ton cost for each route, which consists of the pre-leg transport from a mill to loading port via road or rail, the sea transport from loading port to discharge port and the distribution transport from the port of discharge to the end customer via road or rail. For finding the minimal costs, different loading ports and discharge ports for mills are evaluated in comparison with the current ones. This means that the cost optimization is a rerouting analysis: savings are found only by rerouting a mill’s volumes to a different loading port or to a different discharge port. The new traffic arrangements found in this study, provide an annual cost saving of 4.0% or 8.5% in the entire spend of the short sea shipping-chain of the case company. The first figure is in comparison with 2018-costs, and the latter with 2021-costs, when the new model would be implemented. This is achieved by shortening the pre- and distribution-legs, thus shipping longer distances at sea and shorter distances at land. In addition to the lower costs of the new short sea shipping-chain, literature suggests that the optimized chain is more sustainable, safer and has less negative impacts to society and the economy, because it has less road- and rail kilometers than before. Shipping is the greenest mode of transport in terms of ton-kilometers. The new short sea shipping-chain would also shift the road and rail transport of the intermodal transport chain to shorter and more competitive distances. The European Union and the European Investment Bank also have highlighted the environmental and societal benefits of short sea shipping in their transportation strategies. For the case company, this could be utilized by applying for EU-funding for possible short sea shipping-related investments.
Keywords: Maritime logistics, short sea shipping, shipping costs, forest industry, merilogistiikka, lähimerenkulku, merikuljetuskustannukset, metsäteollisuus